Motivation, giftedness and talent: A challenge to success - Blumen, Sheyla (2008)
Definitions about giftedness and talent involving motivation as a significant variable either in the genesis of giftedness or in the development of intellectual talent are analyzed. An analysis on the influence of motivation in successful achievers, underachievers, as well as in the socialemotional development of the gifted is presented. An update view of the goals achieved by Peru as a country, as well as the actual challenges that faces Peru in the development of giftedness and talent in multicultural and poverty conditions, at the conceptualization, identification, and program levels are presented. Moreover, an economic and viable project of advocacy on the development of giftedness in Peru within the regular educational system along Elementary, Secondary and College level is presented. Finally, conclusions and recommendations for the development of state policies in order to promote giftedness in Peru are presented.